Epithelioid Angiosarcoma of the Septum Pellucidum - Chiara Baldovini; Matteo Martinoni; Gianluca Marucci (Case Reports in Pathology)
Primary cerebral intra-axial epithelioid angiosarcoma is an extremely rare malignancy. To the best of our knowledge we describe the first case of epithelioid angiosarcoma arisen in the septum pellucidum of a 54-years-old man. Albeit extremely rare, this neoplasia is a potential source of misdiagnosis for other aggressive malignant tumors, and it should be taken into consideration.